Firefight - Sanderson, Brandon (New York : Delacorte Press, 2015)
David and the Reckoners continue their fight against the Epics, humans with superhuman powers, except they may have met their match in Regalia, a High Epic who resides in Babylon Restored, the city formerly known as the borough of Manhattan.
Sequel to: Steelheart.
HL 700
Keywords: Supervillains -- Juvenile fiction; Guerrilla warfare -- Juvenile fiction; Science fiction